Teachers' Work in a Globalizing Economy - Dow, Alistair (Taylor & Francis, 2000)
Extended critical case studies provide a tangible working expression of the labour process of teaching, showing how teachers are simultaneously experiencing significant changes to their work, as well as responding in ways that actively shape these processes. For teachers and researchers, this book shows what processes are at work in the global economy which impact on, and sometimes control, the role of the teacher. It also reveals how teachers accommodate, resist or redefine their working circumstances, and explores methods researchers might employ in order to increase our understanding and knowledge of the effect of globalization on teaching.